(untitled) (Sains Humanika, 2024)
This study aims to assess students’ listening skills and gauge their perceptions using the HURIER Model of Listening. The study involved primary school students using purposive sampling, utilizing an experimental research design. Data collection included pre-tests, post-tests and questionnaires. Quantitative data analysis using SPSS version 26 produced descriptive statistical data such as inference, percentage, and mean value. The study found satisfactory effectiveness in students’ listening skills based on the HURIER Model, highlighting its suitability for primary school teaching. The components of the model positively impacted students, suggesting its potential for broader application. In conclusion, this study contributes to the understanding of effective listening skills using the HURIER Model, offering insights for educators and researchers to enhance teaching and learning practices.